A novel titania nanorods‐filled composite solid electrolyte with improved room temperature performance for solid‐state Li‐ion battery. (26th July 2019) - Hua, Song; Jing, Mao‐Xiang; Han, Chong; Yang, Hua; Chen, Hao; Chen, Fei; Chen, Li‐Li; Ju, Bo‐Wei; Tu, Fei‐Yue; Shen, Xiang‐Qian; Qin, Shi‐Biao
Summary: Solid‐state batteries (SSBs) with room temperature (RT) performances had been one of the most promising technologies for energy storage. To achieve a chemical stable and high ionic conductive solid electrolyte, herein, a titania (TiO2 ) (B) nanorods‐filled poly(propylene carbonate) (PPC)‐based organic/inorganic composite solid electrolyte (CSE) was prepared for the first time. It was found that by using TiO2 (B) nanorods, the ionic conductivity of the CSE membrane could be improved to 1.52 × 10 −4 S/cm, the electrochemical stable window was more than 4.6 V, and the tensile strength reaches 27 MPa with a strain less than 6%. The CSE was applied for SSB and showed excellent room temperature electrochemical performances. At 25°C, the LiFePO4 /CSE/Li SSB with 3%TiO2 ‐filled CSE had the first cycle specific discharge capacity of 162 mAh/g with a capacity retention of 93% after 100 cycles at 0.3C. While the NCM622/CSE/Li SSB with 3%TiO2 ‐filled CSE had the first specific discharge capacity of 165 mAh/g with a capacity retention of 88% after 100 cycles at 0.3C. The enhancement effect of TiO2 (B) nanorods could be ascribed that the rod‐like fillers provide more continuous Li‐ion transport path compared with nano particles, and the surface porosity and composition of TiO2 (B) nanorods could also improve the interfacial contact and Lewis acid‐base reaction sites between polymer and fillers. The TiO2 (B) nanorods‐filled CSE with high chemical stability, potential window, and ionic conductivity was promising to meet the requirements of SSBs. Abstract : TiO2 (B) nanorods‐filled PPC‐based composite solid electrolyte was firstly fabricated. TiO2 (B) nanorods enhanced the ambient temperature ionic conductivity. The high‐voltage solid‐state battery shows excellent rate and cycle performance at 25°C.